Consistency of Mycorrhizal Effectiveness on Maize Growth and P Uptake in Two Generations of Pot Culture Using Andisol-Based Media - Vita Ratri Cahyani; Suryanti Suryanti; Slamet Minardi; Widyatmani Sih Dewi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
The functional roles of Arbuscular Mycorrhiza (AM) in soils with P limitations are well documented. However, the protocol to produce effective AM inocula was still limited. This research aims at obtaining the effective AM culture in handling P constraints for maize growth on Andisols. The first experiment of pot culture I was to propagate and examine the effectiveness of AM isolates by using a factorial completely randomized design with two factors, A=media (A0: zeolite; A1: representative media=Andisol Tengaran; A2: typical media=a mixture of Andisol Tengaran+Tawangmangu; A3: typical media+Bio-RP nutrition; A4: Inceptisol) and I = AM inoculum source (I0: no inoculum; I1: AM from Andisol Tengaran; I2: AM from Andisol Tengaran + Tawangmangu; I3: AM from 8 soil types), with six replications. The second experiment investigated the consistency of mycorrhizal effectiveness by reculturing AM cultures generation I to pot cultures generation II with the same composition of the respective media. The combination treatments of A1I3, A2I2, A0I3, and A4I3 (AM cultures generation I), continued by A1I32, A2I22, A0I32, and A4I32 (AM cultures generation II) showed consistently the highest AM infectivity and effectiveness on maize growth and P uptake on Andisol-based media, and on the comparison media of zeolite and Inceptisol media, respectively.